PENGGUNAAN SUSPENSI Baculovirus TERHADAP Oryctes rhinoceros L. (Coleoptera : Scarabaeidae) DI LABORATORIUM - Desmendry Endro Silitonga Desmendry Endro Silitonga; Darma Bakti 2 Darma Bakti 2; Marheni Marheni (Jurnal Agroekoteknologi, 2013)
Use suspense of Baculovirus to Oryctes rhinoceros L. (Coleoptera; Scarabaeidae) in the Laboratory.The objective of this research was to know the suitable suspense of baculovirus to larvae in thelaboratory. This research was conducted in the laboratory of pest, Faculty of Agriculture, Universityof North Sumatra, Medan. Research using completely randomized design (CRD) non factorial with5 treatments and 5 replications. The results showed that the highest percentage of larval mortality(P4) (suspense of Baculovirus, 40/1 liter of water) by 48.00 % and the lowest on P0 (control) andP1 (suspense Baculovirus-infected larvae of O. rhinoceros larvae 5/1 liter of water) of 0.00 % and4.00 %. Key words : palm oil, Oryctes rhinoceros, Baculovirus.